Asthma management with breath-triggered inhalers: innovation through design - Morais-Almeida, M (2020)
Background: Asthma affects the lives of hundred million people around the World. Despite notable progresses in disease management, asthma control remains largely insufficient worldwide, influencing patients' wellbeing and quality of life. Poor patient handling of inhaling devices has been identified as a major persistent problem that significantly reduces inhaled drugs' efficacy and is associated with poor adherence to treatment, impairing clinical results such as asthma control and increasing disease-related costs. We herein review key research and development (R&D) innovation in inhaler devices, highlighting major real-world critical errors in the handling and inhalation technique with current devices and considering potential solutions. Furthermore, we discuss current evidence regarding breath-triggered inhalers (BTI). Main body: The two most common significant problems with inhalers are coordinating actuation and inhalation with pressurized metered-dose inhalers (pMDIs), and the need to inhale forcibly with a dry powder inhaler. BTI R&D plans were designed to overcome these problems. Its newest device k-haler® has several other important features, generating a less forceful aerosol plume than previous pMDIs, with efficient drug delivery and lung deposition, even in patients with low inspiratory flow. The local and systemic bioavailability of fluticasone propionate and formoterol (FP/FORM) administered via k-haler® has been shown to be therapeutically equivalent when administered via the previous FP/FORM pMDI. This device requires very few steps and has been considered easy to use (even at first attempt) and preferred by the patients in a randomized crossover study. In our country, FP/FORM k-haler is available without additional costs compared to FP/FORM pMDI. All devices continue to require education and regular checking of the correct inhalation technique. Conclusion: BTI R&D can bring advantage over current available inhalers, avoiding the two most common identified critical errors in inhalation technique. K-haler® BTI is currently available, without an increased cost, and approved for adolescents and adults with asthma in whom treatment with inhaled combined therapy with long-acting beta2-agonists and corticosteroids is indicated. Its attractive and practical design to facilitate its use has been awarded. K-haler® represents added value through innovation to fulfill actual asthma patient needs, thus with potential relevant impact in asthma management and effective control.